Eliciting local knowledge on barangay disaster risk reduction and management planning through participatory 3-dimensional mapping - Garcia, Emmanuel B.
Contemporary planning praxis calls for bottom-up approach that underscores the importance of a participatory and multi-stakeholder planning process. Crafting effective local plans necessitates the importance of acquiring proper baseline information whilst implementing applicable interventions at the community level. To make effective disaster risk reduction plans and strategies, it is thereby imperative to recognize the different coping mechanisms and capacities as well as the local know-how and resources of a community. This puts the Barangay at the forefront of DRRM initiatives- the barangay being the basic political unit where fundamental DRR decisions have to be instituted. This study aims to showcase the value of local knowledge as an input to local disaster risk reduction and management initiatives through Participatory 3-Dimensional Mapping (P3DM).Eliciting local knowledge for disaster risk reduction requires methodological support that provides the communities the opportunity to participate. P3DM fits this role as it proves to be an effective tool to generate local knowledge through the participatory nature of the process that allows DRR actors to come together and produce tangible outputs useful not only to the community but to the other agencies as well. P3DM further recognizes the value of local knowledge and capitalizes on the importance of participation to provide a better understanding of the unique conditions of each community in time of calamities. Its ability to facilitate the integration of both scientific and local knowledge serves as its comparative advantage over other participatory means. Furthermore, its potential to be translated into GIS renders it useful to all stakeholders of DRR. In a nutshell, a methodology that aspires to be useful for policy formulation should be able to connect to the scale of understanding of the different stakeholders. This has been proven through the P3DM activities conducted in the study area. This research validated the importance of local knowledge in crafting DRR interventions at the barangay level and underscored the need for an effective methodological framework by which local knowledge can be mainstreamed in the process. It has shown P3DM as an effective community-based medium to bridge the gap between scientific and local knowledge which is essential in any DRR framework.